E-Service Quality in Online Zakat and Its Impact on Muzaki Behavior - Kurniawan, Rulli; Kustiawan, Unggul (International Journal of Zakat, 2024)
In the digital era, e-service quality plays a crucial role in determining the success of online businesses, including zakat services. This study explores the impact of e-service quality on customer satisfaction, customer trust and institutional reputation, as well as its effects on customer behaviors such as repurchase intention, word-of-mouth promotion and site revisit. Through an online survey of 250 users of online zakat services and analysis using Structural Equation Modeling (SEM), this research found that usability and service interaction significantly contribute to enhancing e-service quality, which directly increases customer satisfaction and trust. Although customer satisfaction can increase repurchase intention, it does not directly increase word of mouth or site revisit, indicating the important role of other factors such as spiritual values and social recommendations. High e-service quality also strengthens the institution's reputation, underlining the importance of maintaining high online service quality to retain customer trust and loyalty. This study recommends zakat institutions to improve usability and service interaction on their online platforms to strengthen customer relationships. Further research is suggested to explore other variables that influence customer behavior in the context of online zakat.